MAGMATISMO ALCALINO MESOZÓICO NA PORÇÃO CENTRO-ORIENTAL DO PARAGUAI: ASPECTOS GEOCRONOLÓGICOS - Velázquez, V. F.; Gomes, C. B.; G. Capaldi, G.; Comin-Chiaramonti, P.; Ernesto, M.; Kawashita, K.; Petrini, R.; Piccirillo, E. M. (Geochimica Brasiliensis, 2011)
Sem resumo